2021
DOI: 10.1109/access.2021.3068215
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven AI-Based Parameters Tuning Using Grid Partition Algorithm for Predicting Climatic Effect on Epidemic Diseases

Abstract: Adaptive Neuro-fuzzy Inference System (ANFIS) remains one of the promising AI techniques to handle data over-fitting and as well, improves generalization. Presently, many ANFIS optimization techniques have been synergized and found effective at some points through trial and error procedures. In this work, we tune ANFIS using Grid partition algorithm to handle unseen data effectively with fast convergence. This model is initialized using a careful selection of effective parameters that discriminate climate cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Subtractive clustering (SC); where generated clusters are utilized to derive iterative-based optimization clustering to estimate ANFIS parameters. This method has good representation, if high dimensional case is utilized for moderate biometric hand features [26], [33]. Optimization of ANFIS parameters using SC achieved best performance [35].…”
Section: A Adaptive Neuro-fuzzy Inference System (Anfis)mentioning
confidence: 98%
See 3 more Smart Citations
“…Subtractive clustering (SC); where generated clusters are utilized to derive iterative-based optimization clustering to estimate ANFIS parameters. This method has good representation, if high dimensional case is utilized for moderate biometric hand features [26], [33]. Optimization of ANFIS parameters using SC achieved best performance [35].…”
Section: A Adaptive Neuro-fuzzy Inference System (Anfis)mentioning
confidence: 98%
“…ANFIS is an AI approach, composing Artificial Neural Network (ANN) and fuzzy inference networks (FIS) as a single ANFIS model, leveraging individual limitations of ANN and FIS methods [25], [26]. One major advantage of ANFIS is its ability to make good representation of complex and non-linear connections among features [25].…”
Section: A Adaptive Neuro-fuzzy Inference System (Anfis)mentioning
confidence: 99%
See 2 more Smart Citations
“…Kelly et al summarized the harmful effects of air pollution on the respiratory system based on epidemiological and toxicological studies, ranging from the worsening and progression of asthma, allergic rhinitis and chronic obstructive pulmonary disease to lung infections, bronchiectasis and cystic fibrosis [9]. Abdullahi et al used an adaptive neuro-fuzzy inference system to predict the increase in confirmed cases of new crown pneumonia based on climate information [14].…”
Section: Related Work a Medical Data Analyticsmentioning
confidence: 99%